Retrospective comparison of the frequency of Do Not Intubate orders among patients diagnosed with sepsis in the emergency room between 2017 and 2022: DNIs among patients with sepsis in the ER - Tamura, Nobuichiro; Yamamoto, Atsushi; Echigoya, Ryosuke; Ikegami, Tetsunori (Clinical Critical Care, 2024)
Background: This study retrospectively evaluated the frequency of "Do Not Intubate" (DNI) orders in patients with sepsis diagnosed in the emergency room in 2017 and 2022. The objective was to understand the longitudinal adoption of the Advanced Care Planning (ACP) concept over a 5-year span. Methods: We included patients primarily diagnosed with sepsis by emergency physicians at Kurashiki Central Hospital in 2017 and 2022. The primary outcome was the frequency of DNI orders, whereas the secondary outcomes were morbidity and length of hospital stay. We compared the outcomes between 2017 and 2022. Additionally, patient characteristics, such as age, sex, presence of co-resident family members, malignancy status, source of infection, and degree of official care certification were collected. Results: We included 82 and 77 patients with sepsis in 2017 and 2022, respectively. Regarding the primary outcome, 39% (95% confidence interval [CI]: 27-49%) (31/82) of patients with sepsis in 2017 had DNI orders, compared to 44% (95% CI: 33-56%) (34/77) in 2022. There were no significant differences in the primary and secondary outcomes between the two years. The only significant difference noted was in the degree of official care certification among patient characteristics. Conclusion: The frequency of DNI orders remained relatively stable between 2017 and 2022. This suggests that the ACP concept has not yet been widely integrated into the decision-making process for treatment strategies for patients with sepsis.